Indigenous education policy in Malaysia: governmentality, power/ knowledge and discourse - Rosnon, Mohd Roslan; Chinnasamy, Saraswathy (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) was created to give Indigenous peoples the right to determine their own educational system. In article 14 it is stated that, Indigenous peoples have the right to establish and control their educational systems and institutions, providing education in their own languages, in a manner appropriate to their cultural methods of teaching and learning. Since the 56 years of independence, Orang Asli has never been neglected or excluded from the government’s planning in ensuring their education development. Following Foucault’s analytical model, this paper discusses how knowledge that constitutes power highlights the way the governing systems work in Indigenous education policy. Furthermore, this paper also deliberates on participation by the Orang Asli and the power held by them to influence the creation of education policy. Therefore, this paper reviews the current and the past reports from 1995 until 2014 that reflect the shifts in government policy of Indigenous education policy in Malaysia. Evidences from a range of reports, are thoroughly analysed through three main ideas; ‘governmentality’, power/knowledge’ and ‘discourse’ which are analytical approaches by Foucault. Based on this analysis, we can get a clear picture and better understanding about power in terms of participation and also the recognition of Indigenous people’s rights concerning education systems in line with the minimum standards outlined in the UNDRIP.